Barriers to Practice of Rural and Remote Nursing in Canada - Hunt, Steve; Hunt, Elena (European Scientific Journal, ESJ, 2016)
The delivery of rural and remote healthcare has been identified in the literature as a unique and complex working environment for Nursing practice. This Canadian setting integrative review looks at barriers associated with rural and remote nursing. Nine articles were retained after filtering over 200 articles extracted from 4 databases. Critical Appraisal Skills Programme Checklist (CASP) for qualitative research and Quality Assessment Tool for Quantitative Studies (QATQ) were used for assessment of a total sample of N=3402 participants. Four (4) main themes (barriers) were extracted: 1) Professional Isolation, 2) Competing Demands, 3) Lack of Sustainable Continuing Educational Initiatives and 4) Lack of Organizational Support. Following analysis of the demographic data, an emerging theme of an aging workforce was also seen as a potential future barrier to rural nursing practice. Future research is required in order for sufficient and appropriate action to be taken in addressing aforementioned barriers. Recommendations for nursing practice and policy in rural and remote areas revolve around exposing nursing students to rural / remote settings, incentives for new graduate students to practice in these areas, as well as support and educational initiatives encouraging practitioners to work to their full scope of practice.